MODERN MOBILE ACCELEROMETERS APPLICATION ABILITIES AND LIMITATIONS FOR THE SAKE OF VIBRATION PROCESSING IN MACHINERY - I. G. Davydov; S. A. Migalevich; S. U. Vasiukevich; A. V. Tsurko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Technical characteristics of modern mobile accelerometers are evaluated in this paper. Application abilities for these accelerometers and its applicability limitations in distributed diagnostic system application are taken into consideration during the research.